2015
DOI: 10.1371/journal.pone.0134078
|View full text |Cite
|
Sign up to set email alerts
|

Neural Resolution of Formant Frequencies in the Primary Auditory Cortex of Rats

Abstract: Pulse-resonance sounds play an important role in animal communication and auditory object recognition, yet very little is known about the cortical representation of this class of sounds. In this study we shine light on one simple aspect: how well does the firing rate of cortical neurons resolve resonant (“formant”) frequencies of vowel-like pulse-resonance sounds. We recorded neural responses in the primary auditory cortex (A1) of anesthetized rats to two-formant pulse-resonance sounds, and estimated their for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…In the natural world, harmonics and formants are usually considered to be specific structures of an animal's voice, which are related to the richness and spread of the spectral components. Studies on mammals have indicated that neurons in the primary auditory cortex encode the spectral structure of sounds in these brain regions (Fishman, Steinschneider, & Micheyl, ; Honey & Schnupp, ), which are analogous to the CMM and NCM in songbirds (Vates et al, ; Wang, Brzozowska‐Prechtl, & Karten, ). In our results, for time windows shorter than the length of one syllable, Ent and Mfr had strong TSC coefficients compared with the other acoustic factors measured (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In the natural world, harmonics and formants are usually considered to be specific structures of an animal's voice, which are related to the richness and spread of the spectral components. Studies on mammals have indicated that neurons in the primary auditory cortex encode the spectral structure of sounds in these brain regions (Fishman, Steinschneider, & Micheyl, ; Honey & Schnupp, ), which are analogous to the CMM and NCM in songbirds (Vates et al, ; Wang, Brzozowska‐Prechtl, & Karten, ). In our results, for time windows shorter than the length of one syllable, Ent and Mfr had strong TSC coefficients compared with the other acoustic factors measured (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Synchrony-based coding of vowels might be less effective in central nuclei, given lower-frequency synchronization limits compared to the auditory nerve (Joris et al 2004). Central neurons may instead encode vowel formant structure through average discharge rate (Mesgarani et al 2008;Perez et al 2013;Carney et al 2015;Honey and Schnupp 2015), but this hypothesis is untested in background noise. Here, we focus on coding of synthetic vowel-like sounds in the auditory midbrain.…”
Section: Introductionmentioning
confidence: 99%
“…In general, STRF prediction accuracy in auditory cortex tends to be relatively poor compared to lower auditory structures such as inferior colliculus, where nonlinearities and contextual influences are less dominant, and responses to a repeated stimulus are more stereotyped [ 68 70 ]. As discussed elsewhere [ 56 , 71 – 73 ], intertrial response variability imposes an upper limit on prediction accuracy that can be obtained with a linear STRF model. This is because the activity of units with distinctive responses across trials is principally governed by factors other than the stimulus (e.g., contextual effects, top-down influences, measurement noise).…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated here, however, prediction correlations were heavily influenced by statistical correction choices, as well as the temporal resolution of the binned responses and predictions. Many additional methodological choices can influence prediction accuracy results, including the size (or fraction used) of the estimation and validation datasets [ 32 , 56 , 76 ], compensating for spike time jitter [ 77 ], smoothing response/prediction functions or receptive field kernels [ 16 , 72 , 76 ], excluding onset responses [ 72 ], and various technical details regarding stimulus representation approaches [ 78 ]. These factors raise important caveats for evaluating system response linearity [ 70 ], and especially for comparing results across studies obtained with different methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation